La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Music, Geography and the Greatest Rewards: A Geohistorical Analysis on the Prestigious Awards of Céline Dion - Iconic Artist - Jucu, Ioan-Sebastian (Review of Historical Geography and Toponomastics, 2020)
In the present academic research connecting geography and music,a real gap remains in the study of different issues associated with both music and geography and, particularly, to the recent music geographies. This paper advances a new geographical approach in music geography highlighting the relevance of time and space in music, in the artist‟s outstanding contribution to music and in their recognition from the local to the global. Particularly the study is focused on one of the most emblematic music artists of the world, analyzing through a spatio-temporal investigation the prestigious awards achieved by the singer Celine Dion, since this singer remains both a real music legend and an iconic artist gaining multiple awards and thoroughly appreciated and admired for her outstanding contribution to music and global popular culture. The research bases on such specific methods as internet research, visual methodologies, bibliographical analysis and geographic information systems (GIS). The latter is used to provide a professional map illustrating the spatio-temporal distribution of the multiple awards received by Dion the artist. The findings of the research highlight the highest scale of appreciation an artist can receive. The results of the study also suggest that the outstanding contribution of the greatest artists of the world, acknowledged by the highest national, international and global forums, provide significant information about their artistic involvement in the global popular culture. They have a strong relevance both in space and in time, thus labeling different cultural decades and distinct places and spaces throughout the world.